Insights into natural genetic resistance to rice yellow mottle virus and implications on breeding for durable resistance - Odongo, Patrick J.; Onaga, Geoffrey; Ricardo, Oliver; Natsuaki, Keiko T.; Alicai, Titus; Geuten, Koen (Frontiers Media, 2021)
Rice is the main food crop for people in low- and lower-middle-income countries in Asia and sub-Saharan Africa (SSA). Since 1982, there has been a significant increase in the demand for rice in SSA, and its growing importance is reflected in the national strategic food security plans of several countries in the region. However, several abiotic and biotic factors undermine efforts to meet this demand. Rice yellow mottle virus (RYMV) caused by Solemoviridae is a major biotic factor affecting rice production and continues to be an important pathogen in SSA. To date, six pathogenic strains have been reported. RYMV infects rice plants through wounds and rice feeding vectors. Once inside the plant cells, viral genome-linked protein is required to bind to the rice translation initiation factor [eIF(iso)4G1] for a compatible interaction. The development of resistant cultivars that can interrupt this interaction is the most effective method to manage this disease. Three resistance genes are recognized to limit RYMV virulence in rice, some of which have nonsynonymous single mutations or short deletions in the core domain of eIF(iso)4G1 that impair viral host interaction. However, deployment of these resistance genes using conventional methods has proved slow and tedious. Molecular approaches are expected to be an alternative to facilitate gene introgression and/or pyramiding and rapid deployment of these resistance genes into elite cultivars. In this review, we summarize the knowledge on molecular genetics of RYMV-rice interaction, with emphasis on host plant resistance. In addition, we provide strategies for sustainable utilization of the novel resistant sources. This knowledge is expected to guide breeding programs in the development and deployment of RYMV resistant rice varieties.